Creating campus cultures : fostering success among racially diverse student populations - Museus, Samuel D.; Jayakumar, Uma M. (New York : Routledge, 2012)
'Many colleges and universities have not engaged in a critical self-examination and transformation of the cultures of their campuses that can lead to most effectively serving racially diverse student populations. This timely edited collection provides insights into how campus cultures can and do shape the experiences and outcomes of their increasingly diverse college student populations. By cultivating values, beliefs, and assumptions that focus on including, validating, and creating equitable outcomes among diverse undergraduate students, an institution can increase their success. Moving beyond previous explorations of campus racial climates, Creating Campus Cultures addresses the considerable obstacles practitioners face as they attempt to transform entrenched institutional cultures to meet the needs of diverse student bodies. A broad range of chapters include voices of students, new research, practical experiences, and application of frameworks that are conducive to success. This book will help student affairs and higher education administrators navigate this increasingly difficult terrain by providing practical advice on how to foster success among racial minority students and enact long-term, holistic change at any institution'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Minorities -- Education (Higher) -- United States; College environment -- United States; Multicultural education -- United States; Educational equalization -- United States